Stacked chalcogenide metasurfaces for third harmonic generation in the UV range. (1st March 2022) - Vincenti, M A; Gao, J; de Ceglia, D; Frantz, J A; Scalora, M; Litchinitser, N M
Abstract: We show that an appropriately designed chalcogenide metasurface allows the enhancement of harmonic generation in the UV range, a regime that conventional wisdom deems inaccessible because of absorption. Here we exploit a combination of the photonic band structure that forms when stacking As2 S3 metasurfaces, phase-locking, nonlinear dispersion, and improved field localization to enhance third harmonic conversion efficiency. We demonstrate an improvement of two orders of magnitude with respect to the single layer counterpart notwithstanding the fact that the harmonic signal is tuned deep in the absorption range at 285 nm.